Relationship of Organizational Factors to the Implementation Minimum Service Standars in Konawe Regency Health Center - Aswan, Aswan; Saafi, La Ode; Harun, Aziz (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: The initial survey was conducted at 29 Health center in Konawe Regency, it was found that there were several Health center not realizing the overall MSS achievement and there was an accumulation of the average achievement of 12 MSS found in 17 Health center under 80% and all Health center did not implement additional service standards seen from the annual report in Konawe District Health Office. Thus, researchers feel the need to conduct research on the relationship of organizational factors to the implementation of minimum service standards at the Konawe District Health Center. Method: This type of quantitative research has a population of all officers who have roles and responsibilities for the quality of Public health center services by applying Minimum Service Standards in 29 Public health center totaling 174 and a sample of 122 officers. Result: Data analysis and obtained the value of X Count or Chi Square 55.03> from 3.84 or X table and the value of Phi 0.695 which means it has a strong relationship. Conclusion: There is a strong relationship between organizational factors (Resources, Leadership, Compensation, Organizational Structure and Job Design) and Implementation of Minimum Service Standards.